Systematic review of parental love and upbringing - Fernando Savone (Perspectivas Metodológicas​)
In the present systematic review, groups of academic studies from different disciplines related to parental love and its influence on parenting were identified, evaluated, and interpreted, in order to know which are the most worked aspects and therefore the research needs that they detect. the lack or absence. As a method that is growing in use due to the increasing volumes of scientific information, it allows to carry out searches in stages to document the available articles on the subject of love in a systematic way, which generated an inventory of documents derived from the fulfillment of each phase. that evidences an updated treatment. and information available online along with proposed advances to encourage research on this topic and its relationships.